Iqbal's Letters and Philosophy of Ethics, Research and Critical Review - Suhani, Mamuna; Abbas, Waseem; Mustafa Farooq, Ghulam (sourcecoder, 2022)
The history of letter writing in Urdu started from Ghulam Ghos Bekhabar and Mirza Ghalib, both made it easy in style and context. From the beginning of letter writing, the letters are the demonstration of ethical values and various philosophies, especially as we assimilate the letters of Iqbal. It becomes clear that he has not only put forward his philosophies regarding "time and space, life and death, selfhood and brotherhood, unity and faith, divine decree and predestination" etc. But he also discussed ethics and moral values in his letters. This article is an effort to bring forth the moral values and ethical philosophies in the letters of Allama Muhammad Iqbal.